2004
DOI: 10.3354/meps278103
|View full text |Cite
|
Sign up to set email alerts
|

Coral defence against macroalgae: differential effects of mesenterial filaments on the green alga Halimeda opuntia

Abstract: Several studies have shown that the growth of macroalgae is reduced when in contact with corals, but very few have addressed the mechanisms involved. This study provides for the first time an explicative mechanism for the inhibition of algal growth by scleractinian corals. In experimental field contacts between 8 species of scleractinian corals and the green alga Halimeda opuntia, corals extruded their mesenterial filaments (MFs) onto the plant. In some coral species, this extrusion was followed by persistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 43 publications
1
39
0
7
Order By: Relevance
“…Few of these mechanisms are known to occur against algae. However, corals have recently been shown to extrude mesenterial filaments over algae (Nugues et al 2004). Interestingly, the effect of these filaments on the green alga Halimeda opuntia differed depending on coral species and was closely related to the physical properties of the filaments (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Few of these mechanisms are known to occur against algae. However, corals have recently been shown to extrude mesenterial filaments over algae (Nugues et al 2004). Interestingly, the effect of these filaments on the green alga Halimeda opuntia differed depending on coral species and was closely related to the physical properties of the filaments (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it appears that these species can kill coral recruits using mechanisms other than simple shading or abrasion. As the juvenile coral reaches a certain threshold size, defense mechanisms on the part of the coral may come into play, such as the use of mesenterial filaments in reducing the growth and damaging the thalli of neighboring algae (Nugues et al 2004a). It remains unknown how old corals have to be to employ these tactics, but apparently adult P. astreoides do not use this defense mechanism against algae (Nugues et al 2004a).…”
Section: P I N N a T I F I D A C P O I T E A U I L P O L Y C mentioning
confidence: 99%
“…As the juvenile coral reaches a certain threshold size, defense mechanisms on the part of the coral may come into play, such as the use of mesenterial filaments in reducing the growth and damaging the thalli of neighboring algae (Nugues et al 2004a). It remains unknown how old corals have to be to employ these tactics, but apparently adult P. astreoides do not use this defense mechanism against algae (Nugues et al 2004a). Lirman (2001) found that the growth of adult P. astreoides and Montastrea annularis was reduced when caged with Dictyota spp.…”
Section: P I N N a T I F I D A C P O I T E A U I L P O L Y C mentioning
confidence: 99%
“…Non-trophic interactions appear to be comparatively less significant (but see Jones et al, 1994), albeit both positive and negative non-trophic interactions can be a major structuring force under certain conditions (e.g. Dunstan and Johnson, 2003;Nugues et al, 2004).…”
Section: Introductionmentioning
confidence: 99%